2006
DOI: 10.1152/ajpheart.00150.2006
|View full text |Cite
|
Sign up to set email alerts
|

CRP promotes monocyte-endothelial cell adhesion via Fcγ receptors in human aortic endothelial cells under static and shear flow conditions

Abstract: Monocyte-endothelial cell adhesion is a key early event in atherogenesis. C-reactive protein (CRP), a cardiovascular risk marker, is known to stimulate ICAM and VCAM in human aortic endothelial cells (HAEC) and induces monocyte-endothelial cell adhesion. In this study, we examined the mechanisms by which native CRP promotes monocyte-endothelial cell adhesion under static conditions and tested the effect of CRP on adhesion under shear flow. Incubation of HAEC with CRP (Ͼ25 g/ml) upregulated NF-B activity, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 33 publications
3
73
1
1
Order By: Relevance
“…OxLDL and CRP stimulate activated macrophages to release TNF-α, IL-6 and other cytokines that induce vascular and macrophage activation, thus leading to inflammation (26,27). According to the present study, the triple combination reduces the release of these cytokines, which may retard the inflammatory process associated with atherosclerosis.…”
Section: Discussionmentioning
confidence: 53%
“…OxLDL and CRP stimulate activated macrophages to release TNF-α, IL-6 and other cytokines that induce vascular and macrophage activation, thus leading to inflammation (26,27). According to the present study, the triple combination reduces the release of these cytokines, which may retard the inflammatory process associated with atherosclerosis.…”
Section: Discussionmentioning
confidence: 53%
“…We have previously shown that blocking of CD32/CD64 in endothelial cells abrogate effects of CRP [5,10,11,24,28]. Also, recently we showed that CRP induces superoxide anion release in endothelial cells and promotes eNOS uncoupling, this is reversed by inhibition of CD32 and CD64 [5].…”
Section: Discussionmentioning
confidence: 91%
“…Previously, CRP has been shown to mediate its biological effects in endothelial cells and monocyte-macrophages via CD32 and CD64 [3][4][5][10][11][12][24][25][26][27][28]. Thus, we examined the effects of antibodies to CD16, CD32 and CD64 on CRP-induced superoxide anion release and tissue factor activity.…”
Section: Mechanistic Insights For Crp-mediated Superoxide Release Andmentioning
confidence: 99%
“…There is emerging evidence of CRP as a direct and causative factor contributing to development of atherosclerosis (46,47). CRP increases monocyte adhesion to human endothelial cells under flow conditions (48) and is released from vulnerable plaques, where it co-localises with macrophages, oxLDL, and complement factors (49)(50)(51). In human plasma, CRP exists as a cyclic, disc-shaped pentamer of 115 kDa (pentameric pCRP) (40) or as a monomeric or modified mCRP (52,53).…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%